The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/2050640615604543
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of naloxegol in patients with opioid‐induced constipation and laxative‐inadequate response

Abstract: Naloxegol was efficacious, generally safe and well tolerated in the patients with OIC and LIR, while preserving opioid analgesia. ClinicalTrials.gov identifiers: NCT01309841; NCT01323790.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 21 publications
1
63
0
4
Order By: Relevance
“…The pooled analysis of LIR patients [Tack et al 2015] confirmed findings from 04 and 05 controlled studies . A greater incidence of AEs was found in naloxegol 25 mg group (63.1%) compared with 12.5 mg group (50.6%) and placebo (50.0%).…”
Section: Adverse Eventssupporting
confidence: 74%
See 1 more Smart Citation
“…The pooled analysis of LIR patients [Tack et al 2015] confirmed findings from 04 and 05 controlled studies . A greater incidence of AEs was found in naloxegol 25 mg group (63.1%) compared with 12.5 mg group (50.6%) and placebo (50.0%).…”
Section: Adverse Eventssupporting
confidence: 74%
“…A more recent analysis of KODIAC-04 and KODIAC-05 studies demonstrated benefits of naloxegol in patients with inadequate response to conventional laxatives (LIR) [Tack et al 2015]. Patients with LIR were defined as those who, during 2 weeks, had to have reported OIC symptoms of at least moderate severity while taking at least one laxative class for a minimum of 4 days.…”
Section: Overview Of Naloxegol Clinical Studiesmentioning
confidence: 99%
“…In phase III studies, both substances have been shown to be highly effective and tolerable [30][31][32]; both drugs may be combined with all available opioid regimes irrespective of the choices of substance, medication routes, or dosing.…”
Section: Secretagoguesmentioning
confidence: 99%
“…Der erste oral verfügbare Vertreter der PAMO-RA ist Naloxegol, ein pegyliertes Derivat des μ-Opioid-Rezeptor-Antagonisten Naloxon [6]. Die Wirksamkeit und Sicherheit der Behandlung mit Naloxegol wurde in den randomisierten placebokontrollierten Phase-III-Studien KODIAC 4 und KODIAC 5 evaluiert [16,17]. «Naloxegol kann in Bezug auf das eingesetzte Opioid viel einfacher und unkomplizierter angewendet werden als das unspezifische Naloxon», sagte Dr. Wirz im Interview.…”
Section: Pharmanewsunclassified